A Decade in the Making: Examining the Evidence of SoTL Through Promotion and Tenure Artifacts (Teaching and Learning Inquiry, 2022)
The Scholarship of Teaching and Learning (SoTL) aligns with many institutionally espoused values regarding the value of teaching and learning excellence. SoTL has increased in prestige and value in the past decade, but less information about the proliferation of SoTL within one institution is known. Through an examination of 10 years of curriculum vitae submitted for successful promotion and tenure, our study investigated faculty members’ engagement in SoTL over time and differences in engagement by rank, race, gender, discipline, and type of SoTL artifact. Over the 10-year period, the percentage of faculty engaged in SoTL did not differ significantly. We did uncover differences by disciplinary type and race. Faculty were most likely to engage in grants and presentations related to SoTL and least likely to have a peer-reviewed journal artifact. Our findings suggest that although SoTL efforts continue to gain acceptance within the higher education milieu, institutional and disciplinary realities may be powerful determiners of SoTL participation.